1986
DOI: 10.1017/s0043174500026564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Winter Wheat (Triticum aestivum) Straw Mulch Level on Weed Control

Abstract: Research was conducted to determine the effect of winter wheat (Triticum aestivumL.) straw mulch level on weed control in a winter wheat-ecofallow corn (Zea maysL.)-fallow rotation at North Platte and Sidney, NE, in 1981 and 1982. Wheat straw mulch was established at 0, 1.7, 3.4, 5.1, and 6.8 Mg/ha in stubble fields. After application of 1.5 times the recommended rate at corn planting, metolachlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-1-methylethyl)acetamide] concentration remained higher in unmulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 18 publications
6
113
0
3
Order By: Relevance
“…It is generally agreed that increasing the quantity of cover crop residue will decrease the appearance of annual and broadleaved weeds (Buhler et al 1996;Crutchfield et al 1986). This was confirmed in our Table 1 for a description of Bayer codes for weed species study.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally agreed that increasing the quantity of cover crop residue will decrease the appearance of annual and broadleaved weeds (Buhler et al 1996;Crutchfield et al 1986). This was confirmed in our Table 1 for a description of Bayer codes for weed species study.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in available light under surface residue has significant effects on seedling growth; as germinated seeds search for light they exhaust energy reserves and become etiolated, weak, and more susceptible to certain types of herbicide damage (Crutchfield et al, 1986). Light filtered through dead biomass does not change in quality, only intensity (Teasdale and Mohler, 1993).…”
Section: Effect Of Crop Residues On the Growth And Establishment Of Gmentioning
confidence: 99%
“…The amount varies by crop, with small grain crops requiring less (2-8 Mg ha −1 ) and large grains more (6-17 Mg ha −1 ; Greb, 1967;Teasdale et al, 1991;Wicks et al, 1994). For example, in a wheat-maize rotation study Crutchfield et al (1986) found that at least 3.4 Mg wheat straw ha −1 was needed in order to significantly reduce weed biomass, while in a monoculture maize system in Zimbabwe Ngwira et al (2014) found 6 Mg of maize stover ha −1 was needed. In general, a linear increase in biomass results in an exponential decay in the percentage of germinated seeds that successfully emerge, although the exact relationship depends heavily on residue characteristics (Teasdale and Mohler, 2009;Ngwira et al, 2014).…”
Section: Effect Of Crop Residues On the Growth And Establishment Of Gmentioning
confidence: 99%
See 2 more Smart Citations